An Application of Responsibility Accounting With the Budget As A Cost Control Tool at PT. Hearlife Indonesia - Ulfa Zahra; Junawan; Rahima Br. Purba (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
As income grows, it creates complex problems. One of the difficulties experienced by leaders is in terms of supervision and control costs incurred. arise because the leadership cannot directly support the operation as a whole, transactions are increasingmany and varied. As a result of the problems faced by PT. Listen LIVEIndonesia, Management and Assets are required to improve financial managementnamely the improvement of the organizational structure which is realized by the delegation of authorities, duties, responsibilities to the responsibility center carried out through the budget. With a budget, the responsibility center will be able to be controlled and used as a correction to the objectives of PT. Listen LIFE Indonesia. Data collection procedures can be done by observation, interviews / interviews and Documentation. Data analysis is the process of systematically searching and compiling data that obtained from Data Reduction (Data Reduction), Data Display (Data Presentation), and Withdrawal of Conclusions (Verification). Based on the research conducted, it can be said that the application of accounting accountability with the budget as a cost control tool at PT. Listen LIVE Indonesia is still less effective. However, in general PT. HearLIFE Indonesia has met the requirements and characteristics of responsibility accounting which includes structure organization, budget, classification of controlled and uncontrollable costs, code classification, performance measurement standards and the existence of rewards and punishments has been applied. However, in the preparation of the budget there are still many costs that are not can be controlled so that revenue and profit targets do not reach the budget. This too will affect the manager's performance if the realization of costs is above the budget and profit earned under budget.